2005
DOI: 10.1007/s00535-005-1570-7
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of rice extract on Helicobacter pylori infection in a Mongolian gerbil model

Abstract: The rice extract was effective in suppressing inflammation and epithelial cell proliferation in the gastric mucosa in H. pylori-infected Mongolian gerbils. The rice extract has potential to exhibit a protective effect on H. pylori-related gastric mucosal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…A lack of any direct correlation between anti-H. pylori IgG antibody titers and number of colonies was also reported by Murakami et al 37 Canola oil is a traditional cooking oil in many countries. The canolol concentration in crude canola oil is estimated to be 220-1,200 ppm, which could provide doses similar to that used in our study.…”
Section: Discussionmentioning
confidence: 52%
“…A lack of any direct correlation between anti-H. pylori IgG antibody titers and number of colonies was also reported by Murakami et al 37 Canola oil is a traditional cooking oil in many countries. The canolol concentration in crude canola oil is estimated to be 220-1,200 ppm, which could provide doses similar to that used in our study.…”
Section: Discussionmentioning
confidence: 52%
“…Madathawalu showed the highest beneficial effects in management of diabetes among the traditional rice varieties tested in this experiment. Murakami et al (2005) reported that rice has become an interesting candidate as a natural antibacterial agent. The present study was conducted to identify effect of agronomic practices on antimicrobial activity of rice.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown effective in combating the problem associated with gastritis by suppressing damage to the gastric mucosa by Helicobater pyroli in infected Mongolian gerbils 31 . The rice hull smoke extract has been shown to inhibit S. enterica serovar Typhimurium in vitro in a study reported by Kim et al, 39 that protected an infected mice from death. Presently our study strongly suggested the antibacterial activity of the rice varieties with an increased activity of black rice and anti-staphylococcal activity.…”
Section: Minimum Inhibitory Concentrationmentioning
confidence: 96%